Resiliensi Pada Tunadaksa Non Bawaan - Cindy Refika Felanni; Yolivia Irna Aviani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Resilience in non-congenital quadriplegics is the ability of individuals who experience physical disorders or disabilities due to disease, injury, or conditions that arise after birth to overcome pressure, stress, change, or disturbance, as well as the ability to recover after experiencing difficult situations. This research aims to describe resilience in non-congenital quadriplegics. This research uses a qualitative analysis method with Interpretative Phenomenological Analysis (IPA). The data collection technique uses interviews based on an interview guide with two subjects. This research shows the results that both subjects were able to survive and recover from the events experienced from the beginning of facing disability to living their lives today.